2014
DOI: 10.1590/1807-55092014000300377
|View full text |Cite
|
Sign up to set email alerts
|

Análise do impacto do tênis e coturno fornecidos pelo Exército Brasileiro durante a marcha

Abstract: ResumoO objetivo do presente estudo foi comparar a absorção de impacto durante a marcha descalço e com tênis e coturno fornecidos pelo Exército Brasileiro. A amostra foi composta por 20 soldados saudáveis recém-incorporados sem sintomas ou lesões musculoesqueléticas ou neurológicas que interferissem na marcha. Os sujeitos foram instruídos a caminhar em uma plataforma de madeira de 10 metros de comprimento por um metro de largura, com duas plataformas de força (Bertec, EUA) embutidas no centro. O componente ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…Regarding the clinical variables, for males, the predominance of "Orthopedics, Traumatology, and Rheumatology" (33.9%) agreed with the scientific literature, which points to a higher incidence of musculoskeletal disorders in the military populations (Torres et al, 2014;Bravo et al, 2016;Pereira, 2020). Once joining the military, they are subjected to physical tests and training, military training and missions that demand high from the musculoskeletal system, together with the mechanical overload of the weight of the equipment used for long periods during their activities; this set favors the appearance of musculoskeletal problems, acute and chronic (Lappe et al, 2001;Teodoro & Rosas, 2000;Pereira, 2020).…”
Section: Military Ranksupporting
confidence: 74%
See 1 more Smart Citation
“…Regarding the clinical variables, for males, the predominance of "Orthopedics, Traumatology, and Rheumatology" (33.9%) agreed with the scientific literature, which points to a higher incidence of musculoskeletal disorders in the military populations (Torres et al, 2014;Bravo et al, 2016;Pereira, 2020). Once joining the military, they are subjected to physical tests and training, military training and missions that demand high from the musculoskeletal system, together with the mechanical overload of the weight of the equipment used for long periods during their activities; this set favors the appearance of musculoskeletal problems, acute and chronic (Lappe et al, 2001;Teodoro & Rosas, 2000;Pereira, 2020).…”
Section: Military Ranksupporting
confidence: 74%
“…The factors related to the military's activity can influence the individual's health in different ways, determining specific conditions of illness that differentiate them from other professional categories (Dorneles et al, 2017). Among the main factors that contribute to the morbidity of this workforce are stress, which can trigger several psychiatric disorders (with particular attention to a post-traumatic stress disorder, depression, burnout syndrome, and suicide) (Nasioudis et al, 2015;Chaves et al, 2018;Miao et al, 2018), the physical demands of operational and physical military training associated with the overload of equipment used for long displacements/patrols (leading to acute and chronic musculoskeletal injuries) (Milgrom et al, 1985;Lappe et al, 2001;Teodoro & Rosas, 2000;Torres et al, 2014) and the high prevalence of metabolic and cardiovascular diseases (Hilgenberg et al, 2016). However, while the work activity imposes hostile implications on the health of the military, the requirement of physical and health examinations during the selection, training, and career of professionals can provide positive consequences on their life expectancy, creating a paradoxical effect (Hartal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the reduction in plantar pressures shown in our study the combat footwear provided by the Brazilian Army could act as an effective strategy in the reduction of plantar pressure during standing position, potentially reducing the risk of soldiers sustaining such lower limb musculoskeletal injuries as plantar fasciitis. Additionally, Torres et al (34), showed a significant decrease in impact forces during gait utilizing the same combat boot and this further supports their use.…”
Section: Discussionmentioning
confidence: 68%
“…Desde os anos 70, a força de reação do solo (FRS) tem sido usada por vários pesquisadores para quantificar a força externa durante o movimento humano na marcha e corrida. 45 Atualmente, é um dos parâmetros mais investigados na análise da marcha e corrida. 46 Dois dos exemplos mais comuns da terceira lei de Newton, "a toda ação corresponde uma reação de igual intensidade em sentido oposto", são marcha e corrida humana.…”
Section: Avaliação Cinéticaunclassified